UPAYA PEMERINTAH DESA PANDAU JAYA DALAM PENERTIBAN ADMINISTRASI KEPENDUDUKAN TAHUN 2020-2022 - Niken Nurhafifah; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT The village government is the organizer of government affairs and the interests of local communities in the government system of the Unitary State of the Republic of Indonesia. One of the functions of the village government in administering government affairs is to organize population administration. To bring order to population administration, the village government must make efforts. One effort that can be made by the village government is by implementing policies. This research aims to determine the efforts of the Pandau Jaya Village government in controlling population administration in 2020-2022 and to determine the inhibiting factors in controlling population administration in Pandau Jaya Village. The method used is a descriptive method with a qualitative research type. Data collection techniques use interview and documentation methods. The types of data in this research are primary data and secondary data. The analysis technique used is qualitative descriptive data analysis. The results of this research are that the Pandau Jaya Village Government has made efforts to control population administration through implementing the policies of Law Number 24 of 2013 concerning Population Administration, Kampar Regency Regional Regulation Number 8 of 2019 concerning Population Administration, and Pandau Jaya Village Circular Letter Number 470/ PEM/PJ/I/2018 Concerning Village Administration management. In this case, the Pandau Jaya Village Government has carried out policy implementation by conducting outreach to the residents of Pandau Jaya Village. The aim of this outreach is so that residents of Pandau Jaya Village who still have family cards outside Pandau Jaya Village can immediately move their family cards to Pandau Jaya Village. The existence of inhibiting factors means that the efforts made by the Pandau Jaya Village Government in controlling population administration have not achieved their objectives. So until now there are still many residents of Pandau Jaya Village who have family cards outside Pandau Jaya Village. Keywords: Policy Implementation, Population Administration, Inhibiting Factors.